G.I. nightingales : the Army Nurse Corps in World War II - Tomblin, Barbara (University Press of Kentucky, 1996)
"Weaving together information from official sources and personal interviews, Barbara Tomblin gives the first full-length account of the U.S. Army Nurse Corps in the Second World War. She describes how over 60,000 army nurses, all volunteers, cared for sick and wounded American soldiers in every theater of the war, serving in the jungles of the Southwest Pacific, the frozen reaches of Alaska and Iceland, the mud of Italy and northern Europe, or the heat and dust of the Middle East. Many of the women in the Army Nurse Corps served in dangerous hospitals near the front lines-201 nurses were killed by accident or enemy action, and another 1,600 won decorations for meritorious service. These nurses address the extreme difficulties of dealing with combat and its effects in World War II, and their stories are all the more valuable to women's and military historians because they tell of the war from a very different viewpoint than that of male officers. Although they were unable to achieve full equality for American women in the military during World War II, army nurses did secure equal pay allowances and full military rank, and they proved beyond a doubt their ability and willingness to serve and maintain excellent standards of nursing care under difficult and often dangerous conditions